Ortodoksi, ortopraksi og livsform - Nielsen, Bent Flemming ca. (Dansk teologisk tidsskrift, 2016)
Resumé The paper presents a revised version of an oral opposition given on February 24th 2016 occasioned by the presentation of Niels Henrik Gregersens magisterial book, Den generøse Ortodoksi. Konflikt og kontinuitet i kristendommen, 2015, at the Faculty of Theology, University of Copenhagen. The opposition questions the book’s use of the terms Christianity and Orthodoxy, and suggests alternatively a fresh look at the church being an institution and the church offices.